Pemetaan Audiens Film Gie (2005) Dalam Konsep Resepsi Stuart Hall (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2022)
This study focuses on Stuart Hall's Reception Concept in Mapping the Audience Reception (audience) to Gie (2005). The purpose of this study is to describe and analyze related perspectives, opinions, and the concept of Stuart Hall Encoding-decoding. The method used in this research is a qualitative approach with descriptive-explanative type. The theory chosen as a scalpel in analyzing this research is Stuart Hall's Encoding-Decoding Reception Concept. The results of this study reveal that each informant has a different response to the codes and information conveyed by the film Gie (2005). The different responses and perspectives of each informant become knowledge and information in the new study material of sociology, especially sociology of film. However, regarding the effective level of conveying information through films, it is still said to be not optimal due to technological developments and young people's interest in documentary films is decreasing.